Do effective workplace relationships with management and an effective maintenance culture affect organisational safety outcomes? - Novak, J.; Brunetto, Y.; Shacklock, K.; Farr-Wharton, B.; Brown, Kerry (-, 2017)
The issue of safety and longevity of engineering assets is of increasing importance because of their impact when disasters happen. This paper addresses a literature gap by examining the role of workplace relationships in employees' safety behaviour, and builds on the Resilience Engineering (RE) framework by examining some organisational culture factors affecting how employees behave. A Social Exchange framework is used to examine the impact of supervisor-employee relationships, employee commitment to safety practices, and the type of maintenance culture upon employees’ commitment to safety and safety outcomes. Survey data from 284 technical and engineering employees in engineering asset management organisations within Australia were analyzed using Structural Equation Modelling (SEM). Effective employee relationships with management and a proactive maintenance culture were associated with employee commitment to safety culture and safety outcomes. The findings provide empirical support for embedding an effective organisational culture focused on a proactive maintenance approach, along with ensuring employees are committed to safety processes, to ensure safety outcomes and also asset longevity. One study contribution is that good safety outcomes do not develop in a vacuum; instead they are built on effective workplace relationships. Therefore, SET helps to explain the forming of effective safety culture.